Education for collaboration: the influence of the third space on professional boundaries. (19th January 2022) - Knight, Laura; Crampton, Paul; McKeown, Alex; Arora, Arun; Cliffe, Charlotte; O'Keeffe, Catherine; Griffin, Ann
Abstract : The delivery of integrated care requires the establishment of effective professional relationships that foster collaborative working across health systems. Evidence for how to prepare practitioners to work in those settings is limited. By exploring an innovative postgraduate Programme for Integrated Child Health (PICH) this article highlights the conditions by which effective collaboration can be encouraged. Our qualitative evaluation of PICH involved one-to-one semi-structured interviews with 23 postgraduate general practice and paediatric trainees and their mentors. We analysed the data using the concept of the 'third space', where multiple discourses between individuals with diverse professional backgrounds occur, enabling creative exploration of tensions inherent in new ways of working in order to identify enablers and barriers to collaboration. Our analysis identified three themes that enabled collaboration: effective communication, boundary work and educational spaces; and four themes that were barriers: traditional hierarchical professional identities, curriculum design, financial systems and workplace spaces. PICH demonstrated the value of educational spaces and their role in enabling collaborative practice, as participants explored their professional identities and those of other disciplines. Structural factors in the workplace which inhibit collaborative practice were also evident. We conclude by proposing a model for collaborative learning in third spaces based upon the recognition that, while educational programmes alone will not lead to change, they have the potential to inform the development of productive workplace spaces that will be required if collaborative practice in healthcare is to become a reality.